Uruguay : Selected Issues. (IMF Staff Country Reports; Country Report, 2010)
This Selected Issues paper provides a real exchange rate and competitiveness assessment for Uruguay. It looks at the recent developments in key external competitiveness indicators such as the bilateral real effective exchange rates, export volumes, export market shares, export unit values, unit labor costs as well as foreign direct investment performance. The paper pursues an assessment of the real exchange rate following a broad-based strategy of applying four different approaches, including the purchasing power parity approach, the macroeconomic balance approach, the external sustainability approach, and the equilibrium real exchange rate approach.